Characterization of the AARTFAAC-12 aperture array: radio source counts at 42 and 61 MHz. Issue 1 (31st March 2022) - Shulevski, A; Franzen, T M O; Williams, W L; Vernstrom, T; Gehlot, B K; Kuiack, M; Wijers, R A M J
ABSTRACT: Dense aperture arrays provide key benefits in modern astrophysical research. They are flexible, employing cheap receivers, while relying on the ever more sophisticated compute back end to deal with the complexities of signal processing required for optimal use. Their advantage is that they offer very large fields of view and are readily scalable to any size, all other things being equal. Since they represent 'software telescopes', the science cases these arrays can be applied to are quite broad. Here, we describe the calibration and performance of the AARTFAAC-12 instrument, which is composed of the twelve centrally located stations of the LOFAR array. We go into the details of the data acquisition and pre-processing, we describe the newly developed calibration pipeline as well as the noise properties of the resulting images and present radio source counts at 41.7 MHz and 61 MHz. We find that AARTFAAC-12 is confusion limited at 0.9 Jy/PSF at 61 MHz with a PSF size of 17 × 11 arcmin and that the normalized source counts agree with the scaled VLSSr and 6C survey counts. The median spectral index of the sources between the two frequencies we observed at is -0.78. Further, we have used the derived source counts to estimate any excess cosmic radio background, and we do not find evidence for it at our observing frequencies compared to published literature values.